Case report: A compound heterozygous mutations in ARSA associated with adult-onset metachromatic leukodystrophy - Wang, Bing-lei; Lu, Fen-lei; Sun, Yu-chen; Wang, Hui-juan (Frontiers in Neurology, 2022)
Metachromatic Leukodystrophy (MLD) is a rare autosomal, recessively inherited disease caused by the mutations in arylsulfatase A gene (ARSA). ARSA gene is located on chromosome 22q13 containing eight exons. Based on age at onset, three types of MLD are recognized: late infantile, juvenile, and adult types. Adult-onset MLD has an insidious onset after the age of 16 years. Intellectual and behavioral changes, such as memory deficits or emotional instability, are usually the first presenting symptoms. We reported a Adult-onset MLD manifested cognitive impairment progressively due to a compound heterozygous mutations of c.185_186 dupCA (p.D63Qfs*18) and c.154G>T (p.G172C) in the ARSA gene, and found that the c.154G>T (p.G172C) is a novel mutation. Brain magnetic resonance imaging (MRI) revealed symmetrical demyelination of white matter. The ARSA enzymatic activity in leukocytes was decreased. Nerve conduction studies showed evidence of polyneuropathy superimposed upon a diffuse, uniformly demyelinating, sensorimotor polyneuropathy. Family genes revealed that each family member carries one of the two heterozygous mutant genes. She received treatments such as nerve nutrition and intelligence improvement and is currently under follow-up. Our case found a compound heterozygous mutations in the ARSA gene associatied with MLD, and identified a novel mutation gene c.154G>T (p.G172C). It expands the mutation spectrum of ARSA, and also provides an critical clue for prenatal diagnosis of the family.